Evaluasi Dan Perencanaan Pola Pengangkutan Sampah Kecamatan Sukajadi Kota Pekanbaru - Nathaniel, Tiekpho Ivander; Asmura, Jecky; Reza, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Waste is the residue of human activities that form of solid waste. Waste needs to be managed to avoid having a negative impact. One effort to manage a waste is to make the transportation of waste. The purpose of this research is to evaluate the transport of waste and to make plans regarding the transport of waste in the Sukajadi District. Result of this research shows that dump truck that do not doing sweeping and focus on hauling the waste on x, sothe hauling waste can be short and it will increase the amount of waste being transported.Calculating data indicate that waste hauling is effective but it unproductive Productivity of waste hauling activities can be seen at off-route value. Average score off route That value falls below the range of productive waste hauling values. X. The plan is to change the route of waste hauling. Vehicles that changes routes are SHI 31 Rit I and SHI 45 Rit II.the route from the these vehicle was re-planed because it took a long route, thus spending considerable time on the road. SHI 31 Rit I and SHI 45 Rit II change the order of their waste transport routes in oprder to shortenb the route.Keywords: Waste Transportation, Waste transportation route, Waste transportation disances, Waste transportation time